Are environmental regulation tools effective? An analysis based on financial investment of entity enterprises - Niu, Dengyun; Wang, Zhihua; Yang, Songling (Frontiers in Environmental Science, 2022)
Environmental regulation and economic development are consistent in the long run, but there are certain contradictions in the short term. Examining the characteristics of available environmental regulation tools and using them in a way that will align the interests of local governments and enterprises can improve environmental regulation and enhance green transformation and development. This study considers two general types of environmental regulation tools: negative punishment types and positive incentive types. Applying an intermediary effect model and the two-stage least squares method, a sample of Chinese A-share listed companies from 2007 to 2019 is used to test the impact of these different types of environmental regulation tools on the financial investment levels of entity enterprises. The mechanism through which these macro-environmental regulation tools function and the micro-enterprise heterogeneity factors that influence their impact are systematically studied. The results show that negative punishment type environmental regulation tools have a positive impact on the financial investment levels of entity enterprises, while positive incentive type environmental regulation tools inhibit financial investment levels. This impact is formed through managers’ incentive mechanisms referred to as “whipping the fast ox” and “heavy rewards and light punishments.” Factors such as financing constraints, relocation costs, pollution levels, and enterprise scale have heterogeneous effects on these paths. Policy suggestions are offered based on the findings. This study makes a significant contribution to the literature by clarifying the channel through which environmental regulation influences micro-enterprise decision-making. It provides a theoretical basis and policy reference for local government officials as they address the conflict between economic growth and environmental protection in the short term. Moreover, the results offer long-term development decision-making ideas for shareholders and managers in the process of green transformation and upgrading of enterprises.